The Subjunctive Mood: a Linguo-Cultural Approach - Astghik Chubaryan; Ruzanna Karapetyan (Armenian Folia Anglistika, 2009)
The article analyses the subjunctive mood from the linguo-cultural point of view. The communicative functions and functional characteristics which are connected with the cultural make-up and language thinking of Italians are brought out. Parallels are drawn between the characteristics of the use of the subjunctive mood in Italian and English.